The Effect of ELITA on English Writing Learning for College Students - Taufik Arochman; Susanti Malasari; Sukma Shinta Yunianti (Universitas Hamzanwadi, 2023)
The development of computers and information technology today has influenced each individual's work patterns and activities in education, especially in the teaching-learning process. This study aimed to find out the effectiveness of an intervention using ELITA to enhance the academic writing of college students. ELITA is a learning management system that Universitas Tidar uses. It tries to reveal whether there is any effect on the writing ability of the students taught using ELITA media. This study was quantitative research. The sample of this research was 32 students in the English study program at Universitas Tidar. Between the study's beginning and end, they were given two months of treatment. It can be seen in the result of the paired sample t-test that the t-observed (6.038) was higher than the t-table (1.697). The t-test showed that the p-value (Sig.) was 0.000, the significance level was 5%, and the degree of freedom was 31. Therefore, the results showed that there was a significant effect on the writing ability of the students taught using ELITA. The use of ELITA media can be alternative media to support the student's practice writings.